Distribution of trace elements between carbonaceous matter and sulfides in a sediment-hosted orogenic gold system. (1st May 2020) - Wu, Ya-Fei; Evans, Katy; Fisher, Louise A.; Zhou, Mei-Fu; Hu, Si-Yu; Fougerouse, Denis; Large, Ross R.; Li, Jian-Wei
Abstract: Carbonaceous matter (CM) plays a critical role in the formation of sediment-hosted ore deposits, but metal partitioning between CM and associated sulfides remains unclear. Here we use synchrotron X-ray fluorescence microscopy (SXRF), laser ablation–inductively coupled plasma–mass spectrometry (LA–ICP–MS), and nanoscale secondary ion mass spectrometry (NanoSIMS) to characterize the distribution and deportment of trace elements between CM and sulfides from the Daqiao orogenic gold deposit, China. Four types of CM co-existing with different generations of sulfides are recognized: sedimentary CM1 with pyrite polyframboids in black shale host; indigenous CM2 with early- to main-ore pyrite and marcasite; CM3 with main-ore pyrite; CM4 with pyrite porphyroblasts in underlying graphitic schists. The SXRF results reveal that As, Se, Ni, Pb, and Cu are enriched in pyrite polyframboids relative to CM1 in black shales, although a small proportion of As, Pb, Bi, and U is accommodated in the latter. NanoSIMS images show that Au and As are associated with the CM1 matrix within pyrite framboids that are overgrown by recrystallized pyrite rims. Most trace elements are enriched in the newly-formed aggregates of pyrite and marcasite relative to the CM2 rims that formed via the interactions between ore fluids and pre-existing CM2 cores. Gold, As, Tl, Se, and Hg are highly enriched in the main-ore pyrite relative to co-precipitated CM3 veinlets, and this deportment might reflect changes in fluid redox conditions in response to hydraulic fracturing that is the main mechanism of gold deposition. The pyrite porphyroblasts in the schists are enriched in As, Se, Ni, and Cu relative to CM4, but have lower Au, As, Co, Ni, and Pb than sedimentary pyrite framboids. Taken together, we suggest that biological activity causes accumulation of As and Au within CM interstitial to the framboidal pyrite, and that these elements are released during metamorphic recrystallization and hydrothermal replacement. Trace element deportment in hydrothermal CM and sulfides is controlled by a variety of factors such as the fluid chemistry and interaction between indigenous CM and fluids. Our quantitative results provide significant new insights into the complex processes that formed carbonaceous sediment-hosted ore systems worldwide.